Determining cultural implication content analysis of Pinoybaiting youtube videos - Baltazar, Sophia Marie C. (2021)
"Pinoybaiting" was first coined by Filipino content creator MA Buendia to describe an exploitative marketing strategy by foreign content creators that utilities aspects of Philippine culture to bait Filipinos into interacting with their content. Given the specific literature gap on Filipino representations in foreign media, studying Filipino culture as presented in Pinoybaiting videos provides insights on how Filipinoa are understood and presented through the eyes of foreigners. Additionally, it is a relevant phenomenon to study because it is a cross-cultural interaction that takes place on one ofthe most popular social media platforms in the Philippines: Youtube.

In this qualitative study, 25 Youtube videos underwent a content analysis to determine the Filipino cultural elements, clickbait strategies, and presentation themes of culture as employed by Pinoybaiters. Findings show the content creators featured Filipino cultural elements such as traits, media and entertainment, and food; all of them employed five out of six clickbait strategies derived from the Analytical model for detecting clickbait by Bazaco et al. (2019); a new YouTube-specific clickbait strategy was discovered which the researcher has dubbed as "reaction bait"; and they tend to hype, cross-culturally compare, and generalize Filipino culture.

Results indicate that the Pinoybaiting videos serve as positive representations of Filipinos in media, which may be beneficial to counter the prevalent negative representations outlined in a study by Regullano (2014) and may serve to gratify the 'social identity needs of Filipinos. However, there is still a need to evaluate the "exploitation" aspect of the matter and determine whether content creators are simply commodifying their reactions so as to keep up with the competition for views on Youtube.
Keywords: Clickbait -- strategies